Molecular and ecological signatures of an expanding hybrid zone - Wellenreuther, Maren (Ecol Evol, 2018)
Many species are currently changing their distributions and subsequently form sympatric zones with hybridization between formerly allopatric species as one possible consequence. The damselfly Ischnura elegans has recently expanded south into the range of its ecologically and morphologically similar sister species Ischnura graellsii. Molecular work shows ongoing introgression between these species, but the extent to which this species mixing is modulated by ecological niche use is not known. Here, we (1) conduct a detailed population genetic analysis based on molecular markers and (2) model the ecological niche use of both species in allopatric and sympatric regions. Population genetic analyses showed chronic introgression between I. elegans and I. graellsii across a wide part of Spain, and admixture analysis corroborated this, showing that the majority of I. elegans from the sympatric zone could not be assigned to either the I. elegans or I. graellsii species cluster. Niche modeling demonstrated that I. elegans has modified its environmental niche following hybridization and genetic introgression with I. graellsii, making niche space of introgressed I. elegans populations more similar to I. graellsii. Taken together, this corroborates the view that adaptive introgression has moved genes from I. graellsii into I. elegans and that this process is enabling Spanish I. elegans to occupy a novel niche, further facilitating its expansion. Our results add to the growing evidence that hybridization can play an important and creative role in the adaptive evolution of animals.